2021
DOI: 10.1016/j.isci.2021.102619
|View full text |Cite
|
Sign up to set email alerts
|

Expanded human NK cells armed with CAR uncouple potent anti-tumor activity from off-tumor toxicity against solid tumors

Abstract: Despite the remarkable success of chimeric antigen receptor (CAR)-T cells against hematologic malignancies, severe off-tumor effects have constrained their use against solid tumors. Recently, CAR-engineered natural killer (NK) cells have emerged as an effective and safe alternative. Here, we demonstrate that HER2 CAR-expression in NK cells from healthy donors and patients with breast cancer potently enhances their anti-tumor functions against various HER2-expressing cancer cells, regardless of MHC class I expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 60 publications
1
28
0
Order By: Relevance
“…Thus, our results demonstrated that the regulation of NK cell activity is subject to an array of activating and inhibitory receptors including a transferred CAR. This observation is consistent with a recent report that shows that, unlike HER2 CAR-T cells, HER2 CAR-NK cells do not elicit enhanced cytotoxicity against HER2-positive non-malignant human lung epithelial cells due to the recognition of MHC class I molecules [ 47 ]. Our observation further demonstrated that similar to what happens in NK cells, in iNK cells, the integration of the activating and inhibitory signals could also determine the magnitude of CAR-NK cell reactivity.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, our results demonstrated that the regulation of NK cell activity is subject to an array of activating and inhibitory receptors including a transferred CAR. This observation is consistent with a recent report that shows that, unlike HER2 CAR-T cells, HER2 CAR-NK cells do not elicit enhanced cytotoxicity against HER2-positive non-malignant human lung epithelial cells due to the recognition of MHC class I molecules [ 47 ]. Our observation further demonstrated that similar to what happens in NK cells, in iNK cells, the integration of the activating and inhibitory signals could also determine the magnitude of CAR-NK cell reactivity.…”
Section: Discussionsupporting
confidence: 93%
“…Nevertheless, pre-clinical studies demonstrated HER2-specific T lymphocyte cytotoxicity against GBM stem-like cells that was not evident in HER2 - cells [ 139 ]. In addition, HER2-directed CAR NK cells engineered from healthy donors and breast cancer patients have been shown to selectively kill HER2 + tumour cells while avoiding healthy cells in vitro [ 146 ]. HER2 is also currently the only target used for CAR NK cell therapy in human trials for GBM with the CAR2BRAIN study in Germany (clinical trial ID NCT03383978), as mentioned above.…”
Section: Picking a Suitable Target For Gbm Immunotherapymentioning
confidence: 99%
“…This protocol may require further optimization for the transduction of cytokine activated NK cells which are typically more difficult to transduce. However, we have also used the protocol to successfully generate CAR-NK cells from the NK-92 human NK cell line as described in Portillo et al. (2021) .…”
Section: Limitationsmentioning
confidence: 99%
“…We also show how to assess CAR-NK cell anti-tumor function in vitro using a flow cytometry-based killing assay. For complete details on the use and execution of this protocol, please refer to Portillo et al. (2021) .…”
mentioning
confidence: 99%
See 1 more Smart Citation